PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP MINAT BELI ULANG PADA E-COMMERCE TOKOPEDIA - Yoviko Mahardika; Helni M Jumhur (Universitas Bina Taruna Gorontalo, 2023)
the purpose of this research is to find out whether the variables that are factors in this study have a large and significant effect on the increasing number of Shopee users in their interest in buying online shopping. In this research, service quality, price perception and brand image are used as factors that influence buying interest in Tokopedia E-Commerce. With primary data collection techniques obtained directly through filling out questionnaires by Tokopedia users. Researchers collected data using a questionnaire. The research method used to achieve the goal is a quantitative method with multiple linear regression analysis. The criteria for the selected respondents are Tokopedia e-commerce users. In this study using SPSS software in order to help process and analyze data in research. Test results in this study are service quality has a significant influence on repurchase intention on Tokopedia E-Commerce, Price Perception has a significant influence on repurchase intention on Tokopedia E-Commerce,: Brand Image has a significant influence on repurchase intention on Tokopedia E-Commerce, and the results of the F test are Service Quality, Price Perception and Brand Image simultaneously influence repurchase intention. Keywords: brand image, buying interest, e-commerce, service quality, price perception